The variation of the lower anterior facial height and its component parameters among the three over bite relationships (Cephalometric study) - Saba H Al-Zubaidi; Hussain AA Obaidi (University of Mosul, College of Dentistry, 2006)
Aims: To evaluate the genders and over bite subjects group variation for the lower anterior facial height (LAFH) and its component parameters in Iraqi population in Mosul City. Materials and Methods: The study was performed by using measurements on pretreatment cephalometric radiographs of 79 patients, 27 with normal over bite and 26 for each open and deep over bite. The age ranged from 12-16 years with Class I dentoskeletal relationship. Results: The normal over bite group was significantly larger maxillary anterior alveolar ratio and the mandibular anterior and basal height in male when compared with female. Deep bite group appeared significantly larger mandibular anterior alveolar depth in males than in females. The open bite group showed significantly larger interincisal angle in females than in males. Multiple range variation analysis of the lower facial height and its component parameters disclosed no significant differences in these parameters among the over bite groups except that the open bite group was significantly larger mean value in the LAFH and significantly lower mean value in the interincisal angle when compared with normal and deep bite groups. Conclusion: The significant gender variation of the LAFH and its components of the normal over bite group were appeared in maxillary anterior alveolar depth, ratio and mandibular anterior alveolar height; whereas in deep bite group appeared in mandibular anterior alveolar depth, and in open bite group demonstrated in the interincisal angle.